Over two decades of research on the marine RNA virosphere - Meng‐en Liao; Yunyi Xie; Mang Shi; Jie Cui (iMeta, 2022)
Abstract RNA viruses (realm: Riboviria), including RNA phages and eukaryote‐infecting RNA viruses, are essential components of marine ecosystems. A large number of marine RNA viruses have been discovered in the last two decades because of the rapid development of next‐generation sequencing (NGS) technology. Indeed, the combination of NGS and state‐of‐the‐art meta‐omics methods (viromics, the study of all viruses in a specific environment) has led to a fundamental understanding of the taxonomy and genetic diversity of RNA viruses in the sea, suggesting the complex ecological roles played by RNA viruses in this complex ecosystem. Furthermore, comparisons of viromes in the context of highly variable marine niches reveal the biogeographic patterns and ecological impact of marine RNA viruses, whose role in global ecology is becoming increasingly clearer. In this review, we summarize the characteristics of the global marine RNA virosphere and outline the taxonomic hierarchy of RNA viruses with a specific focus on their ancient evolutionary history. We also review the development of methodology and the major progress resulting from its applications in RNA viromics. The aim of this review is not only to provide an in‐depth understanding of multifaceted aspects of marine RNA viruses, but to offer future perspectives on developing a better methodology for discovery, and exploring the evolutionary origin and major ecological significance of marine RNA virosphere.